1992
DOI: 10.1073/pnas.89.22.11059
|View full text |Cite
|
Sign up to set email alerts
|

Preferential elevation of protein kinase C isoform beta II and diacylglycerol levels in the aorta and heart of diabetic rats: differential reversibility to glycemic control by islet cell transplantation.

Abstract: In the present study, we have measured protein kinase C (PKC) specific activities and total diacylglycerol (DAG) level in the aorta and heart of rats, which showed that after 2 weeks of streptozotocin (STZ)-induced diabetes, membranous PKC specific activity and total DAG content were increased significantly by 88% and 40% in the aorta and by 21% and 72% in the heart, respectively. Hyperglycemia was identified as being a causal factor since elevated glucose levels increased DAG levels in cultured aortic endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
509
8
4

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 686 publications
(541 citation statements)
references
References 44 publications
20
509
8
4
Order By: Relevance
“…Although each isoform is expected to perform distinct functions in vivo, little is known about these functions at present. Several lines of evidence suggested that an abnormal activation of PKC, preferentially PKCb isoform, is implicated in the development of vasculoendothelial complications in some pathological conditions (Inoguchi et al, 1992;Wolf et al, 1991). Furthermore, a recent report by Xia et al has indicated that PKCb-speci®c inhibitor could suppress the VEGF-induced proliferation of endothelial cells (Xia et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Although each isoform is expected to perform distinct functions in vivo, little is known about these functions at present. Several lines of evidence suggested that an abnormal activation of PKC, preferentially PKCb isoform, is implicated in the development of vasculoendothelial complications in some pathological conditions (Inoguchi et al, 1992;Wolf et al, 1991). Furthermore, a recent report by Xia et al has indicated that PKCb-speci®c inhibitor could suppress the VEGF-induced proliferation of endothelial cells (Xia et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless hyperglycemia increases diacylglycerol, a strong activator of PKC (Lee et al, 1989, Ishii et al 1998 chronically activated in diabetic tissues (Inoguchi et al, 1992;deRubertis and Craven, 1994). The promoter region of human eNOS gene contains a phorbol ester responsive element (Marsden et al, 1993), suggesting that PKC activation induces eNOS mRNA expression.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies with cultured cells [25] and animal models [17] show enhanced PKC activity is involved in mediating insulin resistance. The activation of PKC has been explained by the finding that the high glucoseinduced glucose metabolism leads to increased synthesis of DAG which in turn activates the corresponding PKC isoforms [26]. Short-term hyperglycaemia was reported to activate PKC isoforms in different cells [17, 25±28] and in isolated rat skeletal muscle [17,18,20].…”
mentioning
confidence: 99%